Structure of Headline Complex in News Media Discourse - A. V. Sineleva (Научный диалог)
The headlines constructions of the news announcement in mass media discourse are analyzed. The purpose of the study is to identify the specifics of syntactic language resources used in the news announcement: from structural, formal description of the method of information representation to the means of expression of the modal and communicative component of statements. The author claims that it is necessary to consider not separate lexical means which, undoubtedly, are dominating in realization of informative function, but constructions from the point of interaction in them lexical and syntactic language levels. The material for the study was the news announcements (more than 900 headlines) of the start page of the Yandex search engine, which ranks first in terms of appeals in the Russian communication space among other search engines. The author’s observations show that simple two-member complete sentences of the active voice are the most active in the news announcement, among the one-member sentences - indefinite-personal, as well as complex conjunctionless and complex sentences with expository semantic relations are active. It is proved that used syntactic means do not violate such criteria of news genres as capacity, conciseness, relevance, factology, compliance with the actual interests of the target audience, and contribute to formation of an optimal communicative environment.